2020
DOI: 10.3390/molecules25102409
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis and Photoluminescence Study of Pyrazolopyridopyridazine Diones and N-Aminopyrazolopyrrolopyridine Diones

Abstract: The newly designed luminol structures of pyrazolopyridopyridazine diones and N-aminopyrazolopyrrolopyridine diones were synthesized from versatile 1,3-diaryfuropyrazolopyridine-6,8-diones, 1,3-diarylpyrazolopyrrolopyridine-6,8-diones, or 1,3-diaryl-7-methylpyrazolopyrrolopyridine-6,8-diones with hydrazine monohydrate. Photoluminescent and solvatofluorism properties containing UV–Vis absorption, emission spectra, and quantum yield (Φf) study of pyrazolopyridopyridazine diones and N-aminopyrazolopyrrolopyridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…7-Amino-1,3-diphenylpyrazolo[3,4-b]pyrrolo[3,4-d]pyridine-6,8(3H,7H)-dione ( 2f ) [ 28 ]: White solid; 83% yield; mp 217–219 °C; 1 H NMR (DMSO- d 6 , 400 MHz) δ 4.55 (br, 2H, N H 2 ), 7.42 (t, J = 7.46 Hz, 1H, Ar H ), 7.49–7.55 (m, 3H, Ar H ), 7.60–7.65 (m, 4H, Ar H ), 8.25 (d, J = 8.08 Hz, 2H, Ar H ), 8.82 (s, 1H, Ar H ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…7-Amino-1,3-diphenylpyrazolo[3,4-b]pyrrolo[3,4-d]pyridine-6,8(3H,7H)-dione ( 2f ) [ 28 ]: White solid; 83% yield; mp 217–219 °C; 1 H NMR (DMSO- d 6 , 400 MHz) δ 4.55 (br, 2H, N H 2 ), 7.42 (t, J = 7.46 Hz, 1H, Ar H ), 7.49–7.55 (m, 3H, Ar H ), 7.60–7.65 (m, 4H, Ar H ), 8.25 (d, J = 8.08 Hz, 2H, Ar H ), 8.82 (s, 1H, Ar H ).…”
Section: Methodsmentioning
confidence: 99%
“…1,3-Diphenyl-7,8-dihydro-3H-pyrazolo [4’,3’:5,6] pyrido[3,4-d] pyridazine-6,9-dione ( 3f ) [ 28 ]: white solid; 84% yield; mp 292–295 °C; 1 H NMR (DMSO- d 6 , 600 MHz) δ 7.43–7.47 (m, 4H, Ar H ), 7.60–7.64 (m, 4H, Ar H ), 8.20 (d, J = 7.88 Hz, 2H, Ar H ), 9.43 (s, 1H, Ar H ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that pyrazolopyridopyridazine diones generally exhibited the stronger fluorescence intensity and possessed a significant substituent effect, particularly for a m -chloro substituent, and that a more planar skeletal conformation led to a higher Φf, similar to that of the standard luminol. They also concluded that the introduction of the pyrazole and pyridine chromophores led to an increase in the conjugation and aromaticity of the synthetized compounds when compared with luminol [ 9 ]. Current approaches on the synthesis and post-functionalization of pyrazolo[1,5- a ]pyrimidines were reviewed by Portilla et al, who have also highlighted the anticancer potential and enzyme inhibitory activity of these compounds, thus providing important insights for the rational and efficient design of new drugs bearing the pyrazolo[1,5- a ]pyrimidine core [ 10 ].…”
mentioning
confidence: 99%